How patients with gout become engaged in disease management: a constructivist grounded theory study - Alyssa Howren; Susan M. Cox; Kam Shojania; Sharan K. Rai; Hyon K. Choi; Mary A. De Vera (Arthritis Research & Therapy, 2018)
Abstract Background Prior qualitative research on gout has focused primarily on barriers to disease management. Our objective was to use patients’ perspectives to construct an explanatory framework to understand how patients become engaged in the management of their gout. Methods We recruited a sample of individuals with gout who were participating in a proof-of-concept study of an eHealth-supported collaborative care model for gout involving rheumatology, pharmacy, and dietetics. Semistructured interviews were used. We analyzed transcripts using principles of constructivist grounded theory involving initial coding, focused coding and categorizing, and theoretical coding. Results Twelve participants with gout (ten males, two females; mean age, 66.5 ± 13.3 years) were interviewed. The analysis resulted in the construction of three themes as well as a framework describing the dynamically linked themes on (1) processing the diagnosis and management of gout, (2) supporting management of gout, and (3) interfering with management of gout. In this framework, patients with gout transition between each theme in the process of becoming engaged in the management of their gout and may represent potential opportunities for healthcare intervention. Conclusions Findings derived from this study show that becoming engaged in gout management is a dynamic process whereby patients with gout experience factors that interfere with gout management, process their disease and its management, and develop the practical and perceptual skills necessary to manage their gout. By understanding this process, healthcare providers can identify points to adapt care delivery and thereby improve health outcomes.